Motives and expectations of platform workers in Poland - Tusińska, Magdalena (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Nowadays in economic literature the increasing popularity of the concept of platform work and gig economy can be observed. Nevertheless, this growth is not accompanied by a sufficient amount of empirical research into this new phenomenon, especially referring to the Polish labour market. Therefore, such studies on this issue are fundamental. Aim: The first aim of the article was to identify the main motives why some people in Poland started rendering services as platform workers. The second one was to assess to what extent the expectations of platform workers in Poland have been met. Results: Based on the analysis of the current world literature and using the method of the diagnostic survey, it was verified which circumstances and features of platform work were crucial to workers in Poland and what reasons led to expectations not being met. It turned out, that income, flexibility and independence are crucial motives. A concern for majority of respondents was low and unstable incomes. Many workers were also disappointed with the apparent flexibility. In general, the expectations of platform workers in Poland seem to be met to a significant extent, which may contribute to the growing acceptance of this form of work and its popularity.